Estrategias pedagógicas para disminuir el comportamiento disruptivo a través del aprendizaje experiencial en las estudiantes de sexto grado de la I.E Politécnico de soledad (2019)
This project is proposed to carry out pedagogical strategies based on learning experiences, therefore, it is expected to reduce the disruptive behavior that affects the correct development of classes. This situation can be observed in the coexistence follow-up book, as teachers have expressed through surveys. The population that was chosen are the sixth grade students of Institución Educativa Politécnico de Soledad. The type of research of this project is explanatory with a quantitative approach, taking as a guide the positivist paradigm because it allows to corroborate a hypothesis through statistical analysis; The research population will be finite and objective. The survey will be used for data collection